Formulation and Implications of the Job Creation Law on Legal Protection in Indonesia's Forestry Sector - Fitri Setiyani Dwiarti; Nurbaiti Syarif; Suhartina Suhartina (Fakultas Hukum Universitas Lampung, 2025)
The forestry sector is significantly impacted by the Job Creation Law, which alters the legal framework governing the sector. This paper explores the formulation of forestry policies under the Job Creation Law and examines its implications for forest protection in Indonesia. A normative juridical research method is employed, focusing on the analysis of relevant theories, doctrines, and statutory regulations. Key changes in forestry sector regulations include the confirmation of forest areas, determination of forest area size, modifications to the designation and function of forest areas, the utilization of production and protected forests, business permits, non-tax state revenues (PNBP), use of forest areas outside forestry activities, and the roles of central and regional governments in forest protection. Additionally, the law revises prohibitions on activities leading to forest destruction and adjusts sanctions and procedural laws concerning forest-related criminal cases. These changes raise concerns regarding the potential for increased forest area conversion, reduced community involvement in forest management, and weakened sanctions, particularly the removal of absolute liability, which may undermine effective forest protection.